RUSSIA AND THE CENTRAL ASIAN COUNTRIES: BILATERAL SECURITY COOPERATION - PARAMONOV, Vladimir; STOLPOVSKIY, Oleg (CENTRAL ASIA AND THE CAUCASUS, 2009)
Retaining its key role in Central Asia (CA)and in the post-Soviet expanse as a whole is one of the main priorities of the Russian Federation’s current policy. Carrying out this strategic task was and still is directly related to the development of security cooperation, which, in addition to being of mutual benefit in the difficult regional and international circumstances, also has a significant political and propagandist effect. Despite the many disintegrating factors that accompanied the sovereign emergence of each of the post-Soviet republics after the collapse of the Soviet Union, their common historical past, as well as economic, cultural, linguistic, and other traditional ties continue to prompt both the Russian Federation and Central Asia to seek co-operation in both collective and national security. Whereby preference goes to bilateral relations since it is this format that implies more specific and practical forms of military cooperation and is more confidential, making it possible to avoid any negative overtones associated with ambitions and mutual lack of understanding that are particularly vividly manifested in the multilateral format.1